Invariant measures for discrete dynamical systems and ergodic properties of generalized Boole-type transformations - Блекмор, Д.; Голеня, Й.; Прикарпатський, А.К.; Прикарпатський, Я.А. (Український математичний журнал, 2013)
Invariant ergodic measures for generalized Boole-type transformations are studied by using an invariant quasimeasure generating function approach based on special solutions for the Frobenius–Perron operator. New two-dimensional Boole-type transformations are introduced and their invariant measures and ergodicity properties are analyzed. Вивчаються ергодичнi мiри для узагальнених перетворень булевoго типу iз використанням пiдходу твiрних функцiй iнварiантних квазiмiр, що базується на спецiальних розв’язках для оператора Фробенiуса – Перрона. Запропоновано новi двовимiрнi перетворення булевoго типу та дослiджено їхнi iнварiантнi мiри та ергодичнi властивостi.